2013
DOI: 10.1021/ma4007347
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics and Mechanisms of Radical-Based Branching/Cross-Linking Reactions in Preformed Polymers Induced by Benzophenone and Bis-Benzophenone Photoinitiators

Abstract: The general mechanism for photo-cross-linking of preformed polymers is studied by comparing the efficacy of monofunctional benzophenone (BP) and bifunctional bis-benzophenone (BP-BP) photoinitiators for inducing radical chain branching reactions in glassy polystyrene (PS) and rubbery poly(n-butyl acrylate) (PnBA). Upon UV irradiation, macroradicals form and initiate a variety of cross-linking and scission reactions. The kinetics and mechanisms of these macroradical reactions were monitored by gel permeation ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(48 citation statements)
references
References 20 publications
3
45
0
Order By: Relevance
“…Hydrogen abstraction rates from phenyl rings in PS are relatively slow, and hydrogen abstraction from the PS backbone promotes chain scission. [17,18] Qualitatively, these observations explain why the photochemical transfer printing process is more successful for a lamella-forming PS-PMMA than for a PMMA cylinder forming PS-PMMA.…”
Section: Transfer Printing From Other Templatesmentioning
confidence: 86%
See 2 more Smart Citations
“…Hydrogen abstraction rates from phenyl rings in PS are relatively slow, and hydrogen abstraction from the PS backbone promotes chain scission. [17,18] Qualitatively, these observations explain why the photochemical transfer printing process is more successful for a lamella-forming PS-PMMA than for a PMMA cylinder forming PS-PMMA.…”
Section: Transfer Printing From Other Templatesmentioning
confidence: 86%
“…Recent experiments described by Carbone et al [18] and Christensen et al [17] have confirmed that benzophenone-mediated grafting reactions are more efficient for poly(alkyl methacrylates) than for PS. Hydrogen abstraction rates from phenyl rings in PS are relatively slow, and hydrogen abstraction from the PS backbone promotes chain scission.…”
Section: Transfer Printing From Other Templatesmentioning
confidence: 92%
See 1 more Smart Citation
“…Methyl trimethylacetate (6) and butyl isovalerate (9) were chosen to represent poly(tert-butyl acrylate) and poly(n-butyl acrylate), respectively. Hydrocarbons 2,2-dimethylbutane (7) and trans-3-hexene (8) Benzophenone (ca 4 mg) was dissolved in 6 mL of an approximately 90 mM solution of model compound (1)(2)(3)(4)(5)(6)(7)(8)(9) in CD 3 CN. The solution was transferred to a quartz tube capable of being inserted into a standard NMR tube, and inert gas was bubbled through the solution for 5 min to remove oxygen.…”
Section: Methodsmentioning
confidence: 99%
“…We have also compared the efficacies of mono-functional benzophenone and a difunctional bis-benzophenone compound for cross-linking a variety of polymers (7). In the latter work, we found that the details of the cross-linking mechanism were dependent on the nature of the polymer studied.…”
Section: Introductionmentioning
confidence: 95%